Microstructural assessment of friction stir joined AA6063/10.5%Sic Al-matrix composite. (2023) - Gahlot, Pardeep; kaushik, Narinder; Hooda, Naveen; Rajkumar; Gupta, Sachin; Kumar Phanden, Rakesh
Abstract: This study analyses the microstructural characteristics of an AA6063/SiC matrix composite that was FS welded through the green welding technology known as FSW. By using the stir casting method, AA6063/10.5 wt% SiC aluminum matrix composite was created. From the constructed composite matrix, specimen plates with a 6 mm thickness were cut and friction stir welded satisfactorily. Using a tool with a transverse velocity of 110 mm/min and a rotational rate of 1100 rpm, FSW was carried out. AISI H13 tool steel was used as tool material and a square pin-shaped tool was manufactured to carry out the FSW. The interfacial test confirmed that FSW generated a considerable drop in the size of reinforced agents and their uniform allocation in the stir region when assessed to the base metal reinforced matrix. The hardening precipitates' development, dissolution, and reprecipitation were all affected by the heat produced during FSW. Enhanced microstructural and mechanical properties were obtained due to the equiaxed well granule configuration and homogenous allocation of SiC constituent parts in the weld zone. The EDAX analysis was carried out to confirm the presence of any silicon oxide segment in the stir zone. The peaks as observed in the EDAX test confirmed that no new chemical constituent part has been formed due to the abrasion heat developed in FSW.